Analysis of Sound Insulation Capability and Modulus Elasticity according to Shape and Composition of Natural Fiber Composite Kayu Galam (Melaleuca leucadendra) - Polyester - Ammar Farhan Rayudi; Firman Sidiq; Sulistijono Sulistijono; Abdi Suprayitno (IPTEK Journal of Proceedings Series, 2018)
Making and testing of sound insulation materials from natural fiber composite (Galam wood fiber and polyester matrix) to analyze sound transmission loss and modulus of elasticity. Wood material chosen due to the availability of abundant so easyily obtained and also a waste Galam wood is wasted in the process of building construction. Natural fiber shape that used is sawdust and wood chips and using unsaturated polyester as matrix. Speciment made in disc shape with 10 cm of diameter and 6 mm thick. Sound intensity measured in insulated room with sound level meter and speaker as sensor and source and run with variation in frequency of transmitted sound wave. With sound transmission loss theory, sound insulating capability could be analyzed. Measurement of modulus of elasticity is needed as a consideration in their application. The result of this research are sound insulation property is less than matrices even the critical frequency was reduced and elasticity was increasing with increasing of the composition of the filler material.